La práctica de valores utilizada como ejes transversales en el proceso de enseñanza aprendizaje en los décimos años de educación básica del Colegio Técnico Jambelí, sección matutina, del cantón Santa Rosa en el año lecitvo 2011-2012. - Romero Campoverde, Jinson Manuel (2012)
Educational policy that includes the practice of values ​​as a crosscutting issue in the teaching-learning process in different areas: such as Language Arts, Mathematics, Science, Social Studies, Culture Aesthetics, English, Physical Education, Computer Science, Electrical and Aquaculture.